2020
DOI: 10.1108/ijssp-10-2019-0212
|View full text |Cite
|
Sign up to set email alerts
|

Linking global consumer culture and ethnocentric consumerism to global citizenship: exploring the mediating effect of cultural intelligence

Abstract: PurposeThis article attempts to understand the impact of global consumer culture and ethnocentric consumerism on global citizenship by identifying the mediating effect of cultural intelligence.Design/methodology/approachThe proposed structural equation model explains the relationship between global consumer culture, ethnocentric consumerism, and global citizenship. The empirical analysis involves an online survey targeted young people in Indonesia context.FindingsThe empirical evidence broadly supports the vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 71 publications
(111 reference statements)
1
12
2
5
Order By: Relevance
“…Followed by metacognitive factor where a moderate correlation was present, while a low degree of correlation between the two variables was observed for the cognitive factor. Pratono & Arli (2020) found that there is a positive impact of cultural intelligence on the acceptance of foreign brands. Summarizing the foregoing, and in the context of the research covered in the paper, the first hypothesis can be formulated: H1: The metacognitive factor of cultural intelligence has a positive statistically significant impact on consumer acceptance of foreign brands.…”
Section: Interconnection Between Cultural Intelligence and Acceptance Of Foreign Brandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Followed by metacognitive factor where a moderate correlation was present, while a low degree of correlation between the two variables was observed for the cognitive factor. Pratono & Arli (2020) found that there is a positive impact of cultural intelligence on the acceptance of foreign brands. Summarizing the foregoing, and in the context of the research covered in the paper, the first hypothesis can be formulated: H1: The metacognitive factor of cultural intelligence has a positive statistically significant impact on consumer acceptance of foreign brands.…”
Section: Interconnection Between Cultural Intelligence and Acceptance Of Foreign Brandsmentioning
confidence: 99%
“…Korzilius, Bucker & Beerlage (2017) emphasizes that is very important to apply adequate behavior in a certain cultural environment. Consequently, behaviors that are suitable in communicating in one cultural situation may be unsuitable in another (Pratono & Arli, 2020). Therefore, people need to be adaptable to a different cultural setting.…”
Section: Interconnection Between Cultural Intelligence and Acceptance Of Foreign Brandsmentioning
confidence: 99%
See 1 more Smart Citation
“…GCC menunjukkan bagaimana konsumen menjadi anggotanya.konsumen global dengan membeli produk dengan simbol budaya di seluruh dunia. Konsumen etnosentris cenderung menolak GC dengan simbol budaya global yang diberikan (Pratono & Arli, 2020) Ada efek negatif EC terhadap kemauan untuk membeli produk asing . Pemahaman budaya mengungkapkan penerimaan terhadap budaya yang berbeda, yang pada gilirannya meningkatkan kemampuan untuk membangun modal sosial dalam konteks lintas budaya.…”
unclassified
“…Pemahaman budaya mengungkapkan penerimaan terhadap budaya yang berbeda, yang pada gilirannya meningkatkan kemampuan untuk membangun modal sosial dalam konteks lintas budaya. CQ berlaku dalam penyesuaian warga global melalui alokasi upaya dan energi dalam pengaturan lintas-budaya yang berusaha disesuaikan oleh para pelaku (Pratono & Arli, 2020). Konsumen individu dapat menjadi cerdas dan etnosentris.…”
unclassified